1994
DOI: 10.1203/00006450-199405000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Bioelectric Impedance and Skinfold Measurements in Predicting Fat-Free Mass Derived from Total Body Potassium in Children

Abstract: University Cl~ildret~'~ Ilospital. Ilci(lc~lhc~r,y, Gcrrtlro~y /F.S., ;\I.G., K.S../ ut~d hr~rcI.ar Rcscw-ch Coltrc~.Kurl.tr~rlrc, Gcrr)lunjv [..I .%.I ABSTRACT. Despite the increasing use of tetrapolar TBK, total body potassium whole-body bioelectric impedance (BI) analysis in the as-CV, coefficient of variation sessment of body composition, its usefulness in estimating RhISE, root mean square error fat-free mass (FFR.1) has not been evaluated in comparison with conventional skinfold anthropometry in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
184
4
19

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(213 citation statements)
references
References 1 publication
4
184
4
19
Order By: Relevance
“…18 Considered by many to be the 'gold standard' for estimating body fatness, DXA measurements have been limited to the research setting because of their complexity and cost. [19][20][21][22][23] Previous studies have reported significant associations between BMI and DXA 9,24,25 and a recent report in Pima Indian children showed significant relations for both BMI and DXA with blood pressure, lipids and fasting insulin.…”
Section: Introductionmentioning
confidence: 91%
“…18 Considered by many to be the 'gold standard' for estimating body fatness, DXA measurements have been limited to the research setting because of their complexity and cost. [19][20][21][22][23] Previous studies have reported significant associations between BMI and DXA 9,24,25 and a recent report in Pima Indian children showed significant relations for both BMI and DXA with blood pressure, lipids and fasting insulin.…”
Section: Introductionmentioning
confidence: 91%
“…Reilly et al (1996) compared four of these equations for the prediction of FFM in pre-pubertal Caucasian children in whom FFM had been measured by hydrodensitometry. Their ®ndings suggested that the equations by Schaefer et al (1994) and Deurenberg et al (1991) underestimated FFM. Among the four equations, Houtkooper's equation provided the closest estimates of FFM with the narrowest con®dence intervals.…”
Section: Discussionmentioning
confidence: 97%
“…Several investigators have reported regression equations to predict FFM from BIA in children (Houtkooper et al, 1992;Deurenberg et al, 1991;Schaefer et al, 1994;Cordain et al, 1988). Some of these reports provided age and sex speci®c equations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations